Effectiveness of Bail-out Mechanism in the Eurozone: Global vs. Pandemic Crisis - Beljić, Marina; Glavaški, Olgica (Anali Ekonomskog fakulteta u Subotici, 2021)
This paper analyses the effectiveness of bail-out mechanisms after the global crisis in comparison to Covid-19 pandemic crisis in the selected Eurozone economies. It seems that in the circumstances of global instability, laissesz-faire rules in economy are not enough, meaning that government interventions are desirable and unavoidable. In the Eurozone, the implementation of bail-out programs is related with the problem of a new “impossible trinity” and no-bail out clause. However, the adopted clause on non-use of the bail-out mechanism has had to be ignored several times in the past, and those implementations of bail-outs are focus of this paper. The research is based on descriptive statistical analysis and fixed panel model specification using available data in relation to the bail-out programs in the period 2011-2020 in selected Eurozone economies. The research shows that governments appear to have learned at least three lessons from the global crisis in relation to the bail-out mechanisms: (a) the need for quick implementation of emergency measures, (b) the bail-out mechanism was effective in reducing the fiscal deficit, however, caused an increase in the public debt, and (c) strengthening the fiscal framework of the Eurozone economies by defining supranational fiscal rules remains the essence of a stronger Eurozone and the European Union.